Innovációmenedzsment az oktatási és gazdasági folyamatokban - Mohácsi, Márta (Közép-Európai Közlemények, 2015)
Economic historians in the 19th century realized that the revival and acceleration of economy is obtainable through the introduction of new products or services, with the formation of a new technology. At the beginning of the 20th century (in 1913) the first big research organizations were founded and innovation engaged into the economic life. By the turn of the 21st century innovation fully entered into the realm of education. Research centers and big companies founded affiliated departments in universities. The publication has the aim of analyzing the threef old relationship of education, research and economy, by placing innovation into the center of research. The essay examines the innovational performance of EU member states. It presents the correlation between education, research and economy, and supports the systems between educational and economic innovation with fresh statistical data. One of the main focus of the essay is the role of foreign languages, and it also examines the student mobility figures in Europe.